Mental Health Promotion for Productivity of Employee at Workplace in Indonesia - Irfani, Adib Mumtaz; Bantarti, Wisni (Indonesian Social Work Consortium (ISWC), 2023)
Existing job opportunities are followed by different responsibilities. The higher the economic growth, the more complex the competition will be, thus making the responsibility for the work even heavier. This condition has a high impact on the potential for the Indonesian people to experience mental health problems which will ultimately have an effect to the productivity of each individual and have a collective impact on the performance of the company. The purpose of this research is to understand the usage of mental health promotion to leverage productivity Employee in Workforce. This study uses a literature review research method or literature review in analyzing and studying cases. The result of this study showed that three strategies for implementing mental health promotion in the work environment, namely Mental health promotion through working motivation and work environment, Mental health promotion through ethical leadership and psychological empowerment, and Mental health promotion through self-efficacy and employee engagement.